The Key Factors of Critical Path Method in Manufacturing Industry Project - Dg Mohd Al Hafidz Bin Ishak (Open University Malaysia, 2021)
Understanding the right project scheduling methodology is essential to ensure project completion on time. This research is addressing problem of project not complete on time due to project scheduling methodology specifically Critical Path Method methodology not entirely understood by project team. Objectives of this research is to identify the advantages and disadvantages of Critical Path Method, to identify success factor of Critical Path Method and to identify elements of Critical Path Method. The scope of this research is on manufacturing industry specifically in electronics sector located in Johor area and respondent consists of project management professionals. A total of 128 project management professionals eligible for the study with response rate of 91.43%. From those responses, 114 responses were valid for the final statistical assessment. The methodology is based on quantitative research approach. Survey has been used as an instrument for data collection while validity statistical analysis and reliability statistical analysis were used to assess collected data. Studies show the reliable advantages of Critical Path Method are assist project team to make an informed decision, delivers a systematic project scheduling, visualize scheduling risk and enhance project flexibility. Study also show reliable disadvantages of Critical Path Method are Critical Path increase when project duration shortens, Critical Path Method become more complex when scope, time and cost creep from initial project charter, Critical Path Method become ineffective to manage when cost and time are too flexible and changes too dynamic. Study also show